Multivessel spontaneous coronary artery dissection: clinical features, angiographic findings, management, and outcomes. (3rd October 2022) - Salamanca Viloria, J; Garcia-Guimaraes, M; Sabate, M; Sanz-Ruiz, R; Macaya, F; Roura, G; Jimenez-Kockar, M; Nogales, J M; Tizon, H; Velazquez, M; Veiga, G; Bastante, T; et al.
Abstract: Background: Spontaneous coronary artery dissection (SCAD) is a rare cause of acute coronary syndrome. The rate of SCAD patients with multivessel (MV) involvement varies between series (6–13%)1, 2. MV SCAD might be potentially associated to a worse prognosis due to a higher ischemic burden compared with patients with single-vessel (SV) involvement. However, comparative data between patients with MV versus SV SCAD is lacking. Methods: The Spanish multicentre nationwide SCAD registry prospectively included 389 consecutive patients from 34 university hospitals. Patients were classified according to the number of affected vessels in two groups: SV or MV SCAD. In-hospital major adverse event (MAE) was defined as a composite of death, myocardial reinfarction, unplanned revascularization, cardiogenic shock, ventricular arrhythmia or stroke. A major cardiac or cerebrovascular adverse event (MACCE) was defined as a composite of death, myocardial reinfarction, unplanned revascularization, SCAD recurrence or stroke. Results: A total of 41 patients (10.5%) presented MV SCAD (Table 1). There were no significant differences between groups regarding age, sex and distribution of most cardiovascular risk factors, with a non-significant trend towards more hypertension in the MV group (49% vs 34%, p=0.06). MV SCAD patients had more often previous history of hypothyroidism (22% vs 11%, p=0.04) and anxiety disorder (32% vs 16%, p=0.01), with a trend towards more fibromuscular dysplasia (50% vs 29%, p=0.12) among those patients screened. MV SCAD patients presented more often with NSTEMI (73% vs 52%, p=0.01). Regarding angiographic findings, MV SCAD patients presented more frequently focal type 3 lesions (19% vs 6%, p<0.01) and fewer type 1 double-lumen lesions (12% vs 21%, p=0.04). The rate of lesions with an impaired initial Thrombolysis In Myocardial Infarction (TIMI) flow 0–1 was lower (14% vs 29%, p<0.01) in MV SCAD. In both groups, most patients were treated conservatively (71% vs 79%, p=NS). We found no significant differences between groups in MAE during admission. At long-term follow-up (median 29 months), there were no significant differences in MACCE between groups (18% vs 12%, p=0.28). However, the rate of stroke was higher in patients with MV SCAD, both in-hospital (2.4% vs 0%, p<0.01) and at follow-up (5.1% vs 0.6%, p=0.01). This finding could be explained by the basal differences found in hypertension and fibromuscular dysplasia between MV and SV SCAD patients. Conclusions: Patients with MV SCAD have some distinctive clinical and angiographic features. We found no significant differences in our primary composite outcomes, both in-hospital and at long-term follow-up, between patients with SV and MV SCAD. Rate of stroke was significantly higher in patients with MV SCAD. Funding Acknowledgement: Type of funding sources: None.